Effect of customer satisfaction on customer loyalty and the moderating role of customer experience in the Nigerian hotel industry - Gawuna, Muhammad Sani (2019)
The dynamism of the hospitality industry has called for the need to have satisfied and loyal customers in order to achieve competitiveness. Therefore, this study aims to propose and validate a customer loyalty model in the hotel sector. Drawing from social exchange theory and confirmation-disconfirmation theory, this study examined the mediating role of customer satisfaction on the relationships among perceived service quality, perceived value, customer engagement, image, and customer experience on customer loyalty. In addition, the moderating effect of customer experience on the relationship between customer satisfaction and loyalty was also examined. Data obtained from 334 guests in the 82 hotels operating in Kano was analysed using PLS-SEM. Findings showed significant direct relationships between perceived service quality, customer satisfaction, image, and customer loyalty. However, perceived value and customer engagement reported an insignificant relationship. It was also found that the direct relationships between perceived service quality, perceived value, customer engagement, image, and customer satisfaction were established. As postulated, the mediating role of customer satisfaction on perceived service quality, perceived value and customer engagement relationships were supported. However, customer satisfaction did not mediate the link between image and customer loyalty. Similarly, moderating relationship of customer experience on customer satisfaction and loyalty was not supported. The use of customer engagement and customer experience in predicting loyalty is a noble contribution to knowledge and hospitality domain. The finding is of immense benefits to the management as it aids toward developing strategies to satisfy their customers and to retain them.